Surgical treatment of active or aggressive aneurysmal bone cysts in children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
The aim of this study was to evaluate functional and radiological results, tumor control, and complications of the surgical treatment of aneurysmal bone cysts (ABCs) in children by extended curettage using a mechanical burr and cauterization, grafting, and internal fixation in specific locations. Sixty-four children [38 males, 26 females, median age=10 years (range, 5-18 years)] with active or aggressive ABCs of long and flat bones were subjected to a median follow-up of 66 months (range, 28-130 months) following surgical treatment. The pathological fracture rate was 72%. Surgical procedures included intralesional extended curettage (92%) or en-bloc resection (8%). Internal fixation was required in 53%. The pathological fractures healed successfully in 8-12 weeks. The median Musculoskeletal Tumor Society (MSTS) score at the last follow-up was 95% (range, 55-100%). Treatment failure (partial healing/recurrence) and complication rates following extended curettage were 7 and 5.2%, respectively. Statistically, the only parameter affecting partial healing and local recurrence was proximity of the lesion to the growth plate (P=0.011). Extended curettage using a mechanical burr and cauterization, grafting, and internal fixation in specific locations can promote healing in most cases of ABC, with low recurrence and complication rates. Copyright (C) 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: aneurysmal bone cyst; extended curettage; surgical treatment; CURETTAGE; RECURRENCE; TUMORS